Age-related clinical and instrumental analysis of malignant tumors of the cervix (Eurasian Medical Research Periodical, 2021)
The aim of the study is to study the clinical, anatomical and morphological features of malignant tumors of the cervix in women of fertile and elderly age. The study was conducted on the basis of retrospective and prospective data of 60 patients with malignant tumors of the cervix. The disease is more common in 52.2-year-old women than in 35-year-olds, and in younger women aged 65-64 years. We can say that in 83.3% of cases in women, the type of cancer with a flat cell suck. It is in older women that this type of cancer develops in the form of an endophyte, which complicates treatment and worsens the prognosis